Quality of life in dialysis patients (Research, Society and Development, 2022)
Chronic kidney disease is highly prevalent in several age groups of the population. When there is a loss of kidney function, renal replacement therapies, such as hemodialysis, are adopted. Therefore, the aim of this study was to evaluate the quality of life of chronic renal failure patients undergoing hemodialysis. The study has a quantitative, descriptive and cross-sectional approach. Data collection occurred through the application of sociodemographic/economic questionnaire, and health conditions, prepared by the researcher, and the instrument Kidney Disease and Quality of-Life Short-Form (KDQOL-SFTM). The absolute frequency and percentage for categorical variables and Spearman's correlation test were used to describe the results. The sample consisted of 49 patients, predominantly male (61.22%), aged between 51 and 70 years (61.22%), married (46.94%) and of white color/race 51.02%. In the 22 KDQOL-SFTM domains evaluated, the highest average score was the domain of "Encouragement from dialysis staff", with an average of 95.92 points. Next came the domains of "Cognitive function", "Quality of social interaction", "Sexual function" and "Symptoms/problems", all with mean scores higher than 80 points. It was found that the factors that negatively interfered with quality of life were the physical aspect and emotional state, inherent conditions of chronic kidney disease and hemodialysis. This study is expected to favor the planning of actions to improve the health service, and to provide professional training to promote the health of this population.